EFEKTIVITAS DAN IMPLEMENTASI REJIMEN BERBASIS DOLUTEGRAVIR PADA PASIEN HIV DI INDONESIA: TINJAUAN TERHADAP OUTCOME KLINIS DAN TANTANGAN PELAYANAN - Faizal Hermanto; Sylvia Octora Dewi (Jurnal Buana Farma, 2026)
Dolutegravir-based regimens, including TLD (Tenofovir-Lamivudine-Dolutegravir), have become the first-line therapy recommended by WHO for HIV treatment. Indonesia has adopted this regimen in accordance with the Minister of Health Regulation No. 23/2022. This review analyzes the clinical effectiveness and implementation of dolutegravir-based regimens in HIV patients based on data from various health facilities in Indonesia. The purpose of this review article is to analyze the clinical outcomes of dolutegravir-based regimens, including viral load suppression, quality of life, and patient adherence. This review was conducted through a comprehensive search in the PubMed and Google Scholar databases for the period 2015-2025. The search query included the keywords “TLD regimen”, “dolutegravir”, “HIV”, “viral load suppression”, “Indonesia”, “clinical effectiveness”, “tenofovir”, and “lamivudine”. Articles were selected based on studies conducted in Indonesian healthcare facilities, involving adult HIV patients receiving dolutegravir-based regimens, and reporting clinical outcomes or program implementation. Six articles met the inclusion criteria and were analyzed. Results showed that dolutegravir-based regimens have good clinical outcomes in various health facilities in Indonesia. Studies in Palembang demonstrated high viral load suppression among patients receiving antiretroviral therapy. Multi-center studies showed significant improvement in quality of life after switching from nevirapine-based to dolutegravir-based regimens. Studies at the primary care level underscored the importance of medication adherence and adequate monitoring. The review concluded that dolutegravir-based regimens demonstrated good clinical effectiveness with diverse outcomes in HIV patients in Indonesia. Implementation requires strengthening viral load monitoring, adherence management, and capacity building at the primary care level.